TINGKAT KEBUGARAN JASMANI SISWA EKSTRAKULIKULER BOLA BASKET MAN 1 PAGARALAM - Awali, Mirza (Jurnal Penjaskesrek, 2019)
This study aims to determine the level of physical fitness in basketball extracurricular students at MAN 1 Pagaralam. This research is a quantitative descriptive study using survey methods. So that it can give an idea of what was examined. The population in this study were all male students who participated in basketball extracurricular activities at MAN 1 Pagaralam, totaling 21 students. How to determine the sample is the saturation sampling technique. The instrument used to measure physical fitness in this study used the TKJI test instrument aged 16-19 years. Data analysis techniques in this study used the norms of physical fitness in TKJI to measure the level of physical fitness in basketball extracurricular students at MAN 1 Pagaralam.The results of the study stated that 0 students (0%) had excellent physical fitness levels, 0 students (0.00%) had good physical fitness levels, 9 students (43.00%) had moderate physical fitness levels, 12 students (57.00%) have less physical fitness level, 0 students (0.00%) have less physical fitness level. it can be concluded that the level of physical fitness possessed by students participating in Extracurricular Basketball in MAN 1 Pagaralam falls into the Less category.